El derecho a la afiliación del trabajador y su afectación en el registro de entrada al Instituto Ecuatoriano de Seguridad Social sin previa fijación del objeto del trabajo. - Chimbo Ayala, Beberlyn Estefany (2024)
The present research work entitled “The Right of Membership Agreement by the Worker and its Affection in the Register of Ecuadorian Social Security without any Previous Limit Object of Work” Gives the importance of showing the Worker's rights, especially the relationship established with the social security done by the Ecuadorian National Social Security (IESS), well its contribution to IESS that are focus to finance benefits like medical help, retirement, sometimes it is partially done, due to some employees do not do all the adequate contributions. It is the Ecuadorian Constitution, one which establishes the necessity of a fair income and the inalienable right to social security, and for that, the Work Ministry has established a basic chart with minimum incomes per area to guarantee the appropriate income, however, some employees do not respect this one they assigned workers the code 06 as “general worker” instead of based in a specific activity, so, this affects the worker’s rights reducing the benefits like unemployment, retirement feed, and the unemployment sure, here the importance to applied the Ministerial Agreement Nro. MDT-2022-234, establishing the minimum chart of basic income and regulating the social contributions made by the worker. The lack of application of this agreement is presented as a problem that generates sub-declarations of contributions to IESS. It pretends to look for a strict accomplishment control of the basic chart by the employee's side to avoid any rights vulnerability, to highlight the importance of guaranteeing the adequate application of laws and agreement to protect the worker’s rights and guarantee the future for them.